Penetration of Ibrexafungerp (Formerly SCY-078) at the Site of Infection in an Intra-abdominal Candidiasis Mouse Model - Lee, Annie (Antimicrob Agents Chemother, 2020)
Ibrexafungerp (IBX), formerly SCY-078, is a novel, oral and intravenous, semisynthetic triterpenoid glucan synthase inhibitor in clinical development for treating multiple fungal infections, including invasive candidiasis. Intra-abdominal candidiasis (IAC) is one of the most common types of invasive candidiasis associated with high mortality largely due to poor drug exposure in infected lesions. To better understand the potential of IBX to treat such infections, we investigated its penetration at the site of infection. Using matrix-assisted laser desorption ionization–mass spectrometry imaging (MALDI-MSI) and laser capture microdissection (LCM)-directed high-pressure liquid chromatography coupled to tandem mass spectrometry (LC-MS/MS), we investigated tissue distribution and lesion-specific drug exposure of IBX in a clinically relevant IAC mouse model. After a single-dose treatment, IBX quickly distributed into tissues and efficiently accumulated within lesions. Drug concentrations of IBX within the liver abscesses were almost 100-fold higher than the serum concentration. In addition, drug penetration after repeated treatment of IBX was compared with micafungin. IBX exhibited robust and long-lasting lesion penetration after repeated treatment. These data indicate that IBX penetrates into intra-abdominal abscesses highly efficiently and holds promise as a potential therapeutic option for IAC patients.